“THE CARPATHIAN MOUNTAINS”: LOVE, FATE, AND EXISTENTIAL TENTIONS IN ALEKSANDR FAYNBERG’S POETIC UNIVERSE - ODILOVA CHAROSXON SHAVKATJON KIZI (TADQIQOTLAR, 2026)
ANNOTATION: This article provides a comprehensive, systematic, and multi- method scholarly analysis of Aleksandr Faynberg’s poem “The Carpathian Mountains.” The study examines the poem’s poetic structure, compositional dynamics, symbolic-semiotic system, ontological and axiological layers, existential tensions, poetics of love and fate, psychological mechanisms of the inner monologue, and socio- philosophical implications. Through images such as the Carpathian mountains, lovers, stars, the Jewish young man, and local Gutsul customs, the poem explores love, destiny, moral responsibility, and the human confrontation with tragic fate. Methodologically, the research relies on structuralism, hermeneutics, semiotics, phenomenology, and existential analysis. The poem is interpreted as a multilayered poetic model articulating the tension between individual desire, social context, and universal fate.